2021
DOI: 10.1021/acscatal.1c03052
|View full text |Cite
|
Sign up to set email alerts
|

C–C Bond Fluorination via Manganese Catalysis

Abstract: β- and γ-fluorinated ketones are desirable moieties in building blocks for bioactive molecules. Recent progress in installing this functionality has centered around ring-opening carbon–carbon bond cleavage/fluorination of strained cycloalkanols, either using precious silver catalysis or superstoichiometric ceric ammonium nitrate (CAN). Careful study of these methods has allowed us to design and develop a general Earth-abundant-element-catalyzed method for remotely fluorinated ketone synthesis via C–C bond clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 69 publications
2
20
0
Order By: Relevance
“…1 H NMR (400 MHz, CDCl 3 ) δ 7.72 (d, J = 6.8 Hz, 2H), 7.58 (t, J = 7.5 Hz, 1H), 7.49 (d, J = 6.2 Hz, 2H), 7.41 (t, J = 7.7 Hz, 2H), 7.29−7.16 (m, 3H), 5.28 (td, J = 6.7, 3.6 Hz, 1H), 3.96 (d, J = 6.6 Hz, 1H), 3.40 (dd, J = 13.0, 3.7 Hz, 1H), 3.08 (dd, J = 13.0, 6.9 Hz, 1H). 13…”
Section: -Hydroxy-1-phenyl-3-(phenylselanyl)propan-1-one (3a′mentioning
confidence: 99%
See 3 more Smart Citations
“…1 H NMR (400 MHz, CDCl 3 ) δ 7.72 (d, J = 6.8 Hz, 2H), 7.58 (t, J = 7.5 Hz, 1H), 7.49 (d, J = 6.2 Hz, 2H), 7.41 (t, J = 7.7 Hz, 2H), 7.29−7.16 (m, 3H), 5.28 (td, J = 6.7, 3.6 Hz, 1H), 3.96 (d, J = 6.6 Hz, 1H), 3.40 (dd, J = 13.0, 3.7 Hz, 1H), 3.08 (dd, J = 13.0, 6.9 Hz, 1H). 13…”
Section: -Hydroxy-1-phenyl-3-(phenylselanyl)propan-1-one (3a′mentioning
confidence: 99%
“…1 4.08 (dt, J = 11.6, 5.7 Hz, 1H), 2.53 (t, J = 6.9 Hz, 1H). 13 General Procedure for the Synthesis of Cyclopropanols 4a− 4t. Under air atmosphere, cyclopropanol derivatives (1, 0.4 mmol, 1 equiv), diphenyl diselenide (2a, 62.4 mg, 0.2 mmol, 0.5 equiv), and I 2 (∼101.5 mg, 0.4 mmol, 1 equiv) in 1.8 mL of DMSO and 0.2 mL of H 2 O were mixed and heated at 80 °C in a heating block for 18 h. After that, the reaction mixture was quenched with water (10 mL) and extracted with ethyl acetate (3 × 10 mL).…”
Section: -((2-fluorophenyl)selanyl)-3-hydroxy-1-phenylpropan-1-one (3c)mentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the single electron oxidation of cyclic alcohols would generate the O-radical, which undergoes an efficient β-scission and carbon–halogen bond formation. 6 Pioneering works by the groups of Flowers, 7 Murakami, 8 Zhu, 9 Lectka, 10 Loh, 11 and West 12 have shown that the ring-strain release of cyclopropanols or cyclobutanols would provide a strong driving force to enable the ring-opening and halogenation. The transformation of unstrained cyclic alcohols is more challenging.…”
Section: Introductionmentioning
confidence: 99%